Reconstruction of the Integration of Knowledge in Dai Education at PTKIN/PTKIS: An Ontological, Epistemological, and Axiological Study - miskanik; susanto (Jurusan Aqidah dan Filsafat Islam Universitas Negri Sunan Gunung Djati Bandung, 2026)
This research aims to analyze and reconstruct the concept of knowledge integration in dai education within State Islamic Religious Universities (PTKIN) and Private Islamic Religious Universities (PTKIS) through ontological, epistemological, and axiological approaches. This study is motivated by the ongoing dichotomous tendency in the development of Islamic education science that separates religious science and general science, thus having an impact on the fragmentation of the dai education paradigm. The research uses a qualitative approach based on library research with data sources in the form of primary literature on the integration of Islamic science and education, as well as relevant contemporary scientific articles. The analysis is carried out through conceptual reduction, thematic categorization, and critical synthesis of the model of knowledge integration in Islamic education. The results of the study show that the integration of knowledge in dai education is not sufficiently understood as a structural merger between religious and general disciplines, but requires a conceptual framework that unites the ontological dimensions (the unity of reality based on monotheism), epistemological (harmonization of revelation and reason), and axiological (orientation of social transformation). This research also offers an integrative conceptual framework for dai education that can be the foundation for curriculum development, interdisciplinary learning approaches, and graduate competency orientation at PTKIN/PTKIS. Thus, the integration of knowledge is understood as an educational paradigm that allows the formation of dai that has a depth of Islamic knowledge as well as sensitivity to the social reality of society.Keywords: knowledge integration, Islamic education, preacher, curriculum reform.